Coeliac Disease Complicating to B Cell Lymphoma and Enterocolic Fistula - Wajeeha Khalid; Jamaluddin (KARACHI MEDICAL AND DENTAL COLLEGE, 2019)
We describe the case of 66 year old male, known case of COPD and type II diabetes mellitus, with a diagnosis of coeliac disease confirmed by the elevated titers of antigliadin and antiendomysium IgG antibodies together with partial villous atrophy in jejunal histology, complicating to diffuse large B cell lymphoma presented as enterocolic fistula. Laparotomy was performed which  included  gastrojejun-  ostomy to bypass the fistula, ileo-ileal anastomosis to prevent obstruction,  and  end-transverse  colos- tomy. Histology was  taken  from  fistulous  tract  following  laparotomy  suspected  high-grade non-Hodgkin's lymphoma. Further supplementary reports showed immunoperoxidase studies that  the  tumor cells are strongly positive for LCA and negative for CD30 and S100.  These  findings  are  sug- gestive of high grade non Hodgkins lymphoma  which  is  confirmed  by  immunohistochemistry  results.  The biopsy showed high  proliferation  and  soft  tissue  infiltration  by  diffuse  large  B-cell  lymphoma  which shows extensive apoptosis secondary to a complication of coeliac disease  presenting  as  enterocoloc fistula.